- #1
Universe_Man
- 61
- 0
I developed a formula for finding pythagorean triples recently, I thought I'd share it just for general novelty:
n+((n-1)/2)^2=((n+1)/2)^2
Where n= odd perfect square
a^2+b^2=c^2
Pythagorean triple set is (a,b,c)
So pythagorean triple set for my formula is:
(sqrt(n),((n-1)/2),((n+1)/2))
If it's restating something old or obvious, let me know.
n+((n-1)/2)^2=((n+1)/2)^2
Where n= odd perfect square
a^2+b^2=c^2
Pythagorean triple set is (a,b,c)
So pythagorean triple set for my formula is:
(sqrt(n),((n-1)/2),((n+1)/2))
If it's restating something old or obvious, let me know.